The high performance and self-powered rGO interlayered Schottky-type photodetector - Kocyigit, Adem; Yaman, Mehmet; Yilmaz, Mehmet; Yildirim, Fatma; Aydogan, Sakir (Elsevier Science Sa, 2026)
Graphene oxide (GO) has gained great interest due to its promising potential in energy storage, biosensors, water treatment, and optoelectronics applications. In this study, we used reduced graphene oxide (rGO) as an interfacial layer between gold (Au) and n-type silicon (n-Si) to fabricate Au/rGO/n-Si Schottky heterojunction for photodetector applications by spin coating technique. The rGO layer was characterized using a scanning-tunneling electron microscope (STEM), x-ray diffractometer (XRD), Raman spectroscopy and x-ray photoelectron spectroscopy (XPS) for confirming its structural behaviors. The surface morphology and absorbance of the rGO/n-Si were studied by field emission scanning electron microscope (FE-SEM) and UV-Vis spectroscopy. The electrical properties of the fabricated Au/rGO/n-Si heterojunction were characterized by current voltage (I-V) measurements under dark condition, changing light power density and various wavelengths. The diode characteristics as well as diode parameters of the Au/rGO/n-Si heterojunction were extracted by thermionic emission theory, Norde and Cheung functions. To understand the photodetection performance of the Au/rGO/n-Si heterojunction, various detector parameters such as responsivity, specific detectivity, ON/OFF ratio were determined and discussed in detail for the case of light power density and various wavelengths. The Au/rGO/n-Si heterojunction exhibited a high rectification ratio of 104 level, a 0.75 eV barrier height and a 1.72 ideality factor. It exhibited high responsivity, specific detectivity and EQE values of 0.43 A/W, 1.06 x 1012 Jones, 90.16 %, respectively, at a wavelength of 590 nm and zero bias. The results highlight that the Au/rGO/n-Si heterojunction can be used as a simple photodetector device in self-powered mode.
Keywords: rGO; Schottky; Photodetector; EQE; Self-powered